Interlocked supramolecular glycoconjugated polymers for receptor-targeting theranostics. Issue 19 (11th February 2016) - Dou, Wei-Tao; Zhang, Yue; Lv, Ying; Wu, Jiatao; Zang, Yi; Tan, Chunyan; Li, Jia; Chen, Guo-Rong; He, Xiao-Peng
Abstract : We report an interlocked supramolecular ensemble formed between a conjugated polymer (CP) and a fluorescent glycoprobe for receptor-targeting cancer cell theranostics. Abstract : We report an interlocked supramolecular ensemble formed between a conjugated polymer (CP) and a fluorescent glycoprobe for receptor-targeting cancer cell theranostics.